1993
DOI: 10.2337/diacare.16.4.575
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance During and After Pregnancy in Nondiabetic Women in an Urban Population in Tanzania

Abstract: We conclude that women during pregnancy in an urban African setting show little change in glucose tolerance. This contrasts with women in both the developed world, where glucose tolerance worsens, and in a rural African environment, where glucose tends to improve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…The majority were descriptive with a range of study designs, including 10 cross‐sectional studies with sample sizes ranging from 189 to 1086 . There were seven prospective studies with sample size ranging from 58 pregnant women recruited during their first trimester to 5026 women recruited during their first antenatal clinic visit and followed until their first post‐natal visit . Furthermore, we found four retrospective studies which were conducted by reviewing hospital delivery registry .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority were descriptive with a range of study designs, including 10 cross‐sectional studies with sample sizes ranging from 189 to 1086 . There were seven prospective studies with sample size ranging from 58 pregnant women recruited during their first trimester to 5026 women recruited during their first antenatal clinic visit and followed until their first post‐natal visit . Furthermore, we found four retrospective studies which were conducted by reviewing hospital delivery registry .…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed six studies from East and Central Africa: four were conducted in East Africa (Tanzania and Ethiopia) and two in Central Africa (Cameroon and Congo) . The oldest study was a community survey in rural Tanzania in 1989 reporting no existence of GDM in the study population (0%) , and the most recent study was published in 2014 on rural and urban clinics in Tanzania reporting a prevalence of 1% (95% CI: 0.2–2.9) and 8.4% (95% CI 6.3–10.9), respectively, using World Health Organisation diagnostic criteria .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies in the early 1990s found no evidence of impaired glucose tolerance among pregnant Tanzanian women [14,15]. The present results also suggest that elevated glucose levels are rare among pregnant women in Dar es Salaam, although a conservative definition of exposure was adopted because information was lacking on the timing of meal consumption prior to the glucose test.…”
Section: Discussionmentioning
confidence: 42%
“…Estimates of the prevalence of gestational diabetes in this region are scarce and have varied from 0% to 13.9% [1,1113]. Impaired glucose tolerance, a precursor to diabetes, has been reported as 0% among pregnant women in Tanzania [14,15] and 7.3% among those in South Africa [16]. …”
Section: Introductionmentioning
confidence: 99%
“…Zwei weitere Studien aus Tansania berichten von ähnlichen Ergebnissen, jedoch war auch hier die Anzahl der Studienteilnehmer relativ gering (89 bzw. 189) [21,22] .…”
Section: Die Dynamik Des Schwangerschaftsdiabetes In Ostafrikaunclassified